Spindle cell carcinoma in the maxilla: A rare case and literature review - M Varshini; Varsha Salian; Pushparaja Shetty; Shalini Krishnan (Wolters Kluwer Medknow Publications, 2019)
In India, oral squamous cell carcinoma accounts for 90%-95% of oral malignancies. The WHO classifies spindle cell carcinoma (SpCC) under malignant epithelial tumors of squamous cell carcinoma (SCC) and is a rare entity accounting for only 1% of SCCs. It is an aggressive biphasic neoplasm exhibiting high mortality rate owing to increased metastasis and recurrence which signifies the need for recognition and treatment of this perplexed tumor. We present a case of maxillary SpCC where histopathological evaluation alone was indecisive, requiring immunohistochemistry for confirmation of the diagnosis.